Sleep, physical activity and sedentary time in team sport athletes in the northeast of Iceland - Ýr Arnardóttir, N.; Taehtinen, R. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Sports have been associated with various health benefits, however when it comes to the highest level, they become physically and mentally demanding for the athlete [1] and occasionally affects sleep [2]. The aims of the study were to examine whether insomnia affects team sport athletes in the Northeast (NE) of Iceland, and to compare the amount of physical activity and sedentary time of these athletes with comparable groups of people in the same region. METHODS: Sleep, physical activity and sedentary time were measured using a questionnaire for team sport athletes in NE of Iceland and a general population sample in comparison. The Insomnia Severity Index was used to diagnose insomnia. In total, 84 athletes from team sports, men (57.1%; Mean age=22.2, SD=4.1) and women (42.9%; Mean age=23.8, SD=5.9) participated. Participants were aged 18-45 years and competed with a team at the highest level in their sport (football, n=34, 40.5%; handball, n=18, 21.4%; basketball, n=15, 21.4%; volleyball, n=10, 11.9% and ice hockey, n=7, 8.3%). The general population consisted of 189 participants, men (32.8%, Mean age=36.9, SD=6.1) and women (67.2%, Mean age=38.8, SD=5.65) living in the NE of Iceland. RESULTS: In total, 85.6% of the athletes slept 7 to 9 hours per night on weekdays, compared to only 61.5% of the general population. On weekends, 92.7% of the athletes slept 7 to 9 hours per night, compared to only 76.9% of the general population. For the athletes, 36.1% had subthreshold insomnia compared to 48.1% of the general population. Also, 9.6% of the athletes had clinical insomnia compared to 16.9% of the general population. Sedentary time was generally higher among the general population, with 28.8% spending an average of 8 to 10 hours per day sedentary, compared to 27.7% of the athlete group. 11.0% of the general population spent 11 to 13 hours per day sedentary, but only 3.6% of the athlete group. A high proportion of the general population did not meet the recommendations for physical activity, only 26.1% were physically active for 30 minutes per day at least five days per week, while 80.8% of athletes met the recommendations. CONCLUSION: Team sport athletes in NE of Iceland are generally healthy in terms of sleep, physical activity and sedentary lifestyle compared to the general population.